Psychiatric Disorders Secondary to Neurometabolic Disorders (2018)
Some diseases secondary to inborn errors of metabolism are associated with psychiatric disorders or minor neurological symptoms. The existence of some cases with exclusively psychiatric symptoms represents a diagnostic and therapeutic challenge. The aim of this article is to describe seven treatable neurometabolic disorders that should be taken into account in the psychiatric consultation as they manifest with psychiatric symptoms that mask the organic origin of the disorder. Homocysteine metabolism and urea cycle disorders, Wilson's disease, Niemann-Pick disease Type C, acute porphyria and cerebrotendinous xanthomatosis are described. Following an analysis of the literature, a list of psychiatric symptoms associated with these disorders are proposed, ranging from insidious changes in affective state and thought to atypical symptoms such as visual hallucinations, as well as paradoxical effects of antipsychotics or behavioural disorders in children and adolescents associated with loss of autonomy. The most frequently associated neurological signs, such as alterations in the state of consciousness, motor behaviour and balance disorders, catatonia or progressive cognitive deficit are also listed. Emphasis is placed on the importance of considering resistance to antipsychotic treatment as a warning sign to suspect organicity, as well as the significant improvement in psychiatric impairment when effective and early treatment is established. © 2017 Asociación Colombiana de Psiquiatría